Montgomery T-tube for the Management of Postintubation Tracheoesophageal Fistula with Synchronic Subglottic Laryngotracheal Stenosis - Li, Zhigang; Zhong, Chenxi (The Thoracic and Cardiovascular Surgeon Reports, 2014)
A postintubation tracheoesophageal fistula (TEF) complicated with subglottic laryngotracheal stenosis (SLTS) is a challenge to surgical repair. Laryngotracheal resection and primary reconstruction could result in treatment failure. In this report, we describe the successful management of two cases of postintubation TEF complicated with SLTS using a Montgomery T-tube because of the patients' contraindications for laryngotracheal resection and primary anastomosis.
Keywords: thoracic surgery; airway; larynx